Analyses of total economic benefit of improved solid waste management in Lagos city: a DC-CVM approach - Sharaai, Amir Hamzah; Onukogu, Humphrey Francisco; Abd Manaf, Latifah; Mathew, Nitanan Koshy; Adamu, Abdullahi (Kalpana Corporation, 2024)
Waste management is a major economic burden that consumes significant proportion of municipalities' budgets in many parts of the world. Materials that are wasted and abandoned as waste due to inefficient utilisation of limited resources. This study aims to establish a clear rationale for making waste management a priority, by providing an organized and logical set of steps to determine the economic benefit of improvement on management of solid waste management in Lagos city. Multi-stage probability was employed in sampling techniques in selecting target respondents using face-to-face method of questionnaire administration in this study. The questionnaire data collected were analysed with the aid of computer software pages including SPSS version 23, NLOGIT version 5.0 econometric software. The result obtained revealed the importance of demographic variables, which include age, income, family size and years in the area, house ownership as well as bid amount as important determinants of willingness to pay. The result also shows that the households were willing to pay an average amount of N 4112.73 for improved solid waste management in Lagos. The study result provides policy guide on the optimal amount the households will be willing to pay for management of solid waste.